Environmental Gradients in Lizard Colouration - Lekshmi B. Sreelatha; Pedro Tarroso; Ossi Nokelainen; Zbyszek Boratyński; Miguel Angel Carretero (Ecology and Evolution)
ABSTRACT Environmental pressures shape animal colouration, facilitating adaptation to local conditions. However, the extent to which climatic gradients drive colour variation in a species across its distributional range remains unclear. Here, we tested whether the dorsal colouration of Lusitanian wall lizards (Podarcis lusitanicus) varies spatially in response to environmental gradients across its distribution in the north‐western Iberian Peninsula. We estimated dorsal colour brightness (i.e., lightness) from multispectral photographs of 463 animals, originating from 21 locations distributed across the species range. We studied direct and indirect (mediated by body mass) relationships between environmental variables and the lightness of lizards, by piecewise structural equation modelling. We simultaneously tested predictions from Gloger's (darker colouration in warm and humid environments), thermal melanism (darker colouration in colder environments), photoprotection (darker colouration in areas with higher intensity of solar radiation) and Bergmann's (larger body size in colder environments) hypotheses. We found that the lightness of lizards best follows predictions of Gloger's hypothesis for humidity, but not supporting the photoprotection hypothesis, independent of the populations' shared ancestry and geographic location. We found no support for direct thermal melanism, as temperature was not directly associated with lightness. Instead, the indirect effect of temperature on lightness through body size was detected. Consistent with Bergmann's hypothesis, lizards in colder regions tended to be larger and darker. Our study indicates that the evolution of lizard dorsal colouration is driven by variable climatic factors. Experimental tests are necessary to assess the mechanisms driving climatic effects on colouration across diverse environments, advancing beyond the simplistic correlations suggested by ecogeographic hypotheses.